On Indexicality, Direction of Arrival of Sound Sources, and Human-Robot Interaction - Ivan Meza; Caleb Rascon; Gibran Fuentes; Luis A. Pineda (Journal of Robotics)
We present the use of direction of arrival (DOA) of sound sources as an index during the interaction between humans and service robots. These indices follow the notion defined by the theory of interpretation of signs by Peirce. This notion establishes a strong physical relation between signs (DOAs) and objects being signified in specific contexts. With this in mind, we have modeled the call at a distance to a robot as indexical in nature. These indices can be later interpreted as the position of the user and the user herself/himself. The relation between the call and the emitter is formalized in our framework of development of service robots based on the SitLog programming language. In particular, we create a set of behaviours based on direction of arrival information to be used in the programming of tasks for service robots. Based on these behaviours, we have implemented four tasks which heavily rely on them: following a person, taking attendance of a class, playing Marco-Polo, and acting as a waiter in a restaurant.